Nobles and amateurs in the exhibitions of the Real Academia de Bellas Artes de San Fernando (1793-1808) - González-Ramos, Roberto (Arte, Individuo y Sociedad, 2020)
The Real Academia de Bellas Artes de San Fernando organized annual exhibitions in its halls since 1793. These exhibitions, one of the first events of this kind organized institutionally in Spain, showed the public the works of disciples and profesional artists with regularity, in its first period between that year until 1808, after which there was an interruption caused by the Peninsular War. It has been possible to state that among the names of the artists who exhibited their works in these exhibitions, there are many of a new and relevant category: the amateurs. This article focuses on the analysis, from a sociological perspective, of the class origins, gender, number, ages and other characteristics of these amateurs, as well as the reasons for their participation in the exhibitions. A large part of those amateurs were people belonging to the nobility, which is extremely interesting when assessing their incursion into the world of visual arts.